The Identification of the Genetic Components of Autism Spectrum Disorders 2017 - Merlin G. Butler (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
This textbook is dedicated to the study of genetic factors contributing to autism and includes a collection of original research and review articles related to this topic. Autism spectrum disorders (ASD) include a collection of neurodevelopmental disorders characterized by three recognized behavioral domains involving difficulties in communication, social interaction and repetitive behavior. ASD affects 1 to 2 percent of children and is on the increase worldwide. Significant genetic contributions and mechanisms underlie the causation of ASD. Advances in genetic technology and better awareness have led to a diagnosis of 50 to 70 percent of individuals with ASD primarily due to chromosomal abnormalities, submicroscopic deletions or duplications now identified with high-resolution microarray analysis, next-generation DNA (exome) sequencing of gene variants or mutations, recognized single gene disorders or metabolic disturbances. Through discovery by searching genomic databases and peer-reviewed research articles, nearly 800 genes have been identified to contribute to ASD. Highlights in the field of autism research, discovery and identification of genetic components with characterization will be addressed. Furthermore, reviews of current understanding of the causes and diagnostic approaches for ASD and related syndromes will be presented along with discussion of psychiatric/behavior comorbidities and related features, environmental risk factors, parental attitudes and treatment.